Large‐Area Ultrabroadband Absorber for Solar Thermophotovoltaics Based on 3D Titanium Nitride Nanopillars. Issue 22 (21st September 2017) - Chirumamilla, Manohar; Chirumamilla, Anisha; Yang, Yuanqing; Roberts, Alexander S.; Kristensen, Peter Kjær; Chaudhuri, Krishnakali; Boltasseva, Alexandra; Sutherland, Duncan S.; Bozhevolnyi, Sergey I.; Pedersen, Kjeld
Abstract: Broadband absorbers, with the simultaneous advantages of thermal stability, insensitivity to light polarization and angle, robustness against harsh environmental conditions, and large area fabrication by scalable methods, are essential elements in (solar) thermophotovoltaics. Compared to the noble metal and multilayered broadband absorbers, high‐temperature refractory metal‐based nanostructures with low‐Q resonators are reported less. In this work, 3D titanium nitride (TiN) nanopillars are investigated for ultrabroadband absorption in the visible and near‐infrared spectral regions with average absorptivities of 0.94, over a wide range of oblique angles between 0° and 75°. The effect of geometrical parameters of the TiN nanopillars on broadband absorption is investigated. By combining the flexibility of nanopillar design and lossy TiN films, ultrabroadband absorption in the visible and near‐infrared is obtained. A thin layer of hafnium oxide is deposited to enhance the thermal stability of TiN nanopillars. Finally, the thermal/spectral stability of the TiN nanopillars is demonstrated after annealing at 1473 K for 24 h while retaining their structural features. Thus, the TiN nanopillars can provide excellent opportunities for high‐temperature applications, especially solar thermophotovoltaics. Abstract : The thermal stability of the broadband absorbers at high temperatures plays a central role in (solar) thermophotovoltaics. 3D refractory titanium nitride (TiN) nanopillars are demonstrated for ultrabroadband absorption in the entire solar spectral range with unprecedented thermal stability at 1473 K and negligible sensitivity to light polarization and incidence angles. TiN nanopillars can easily be implemented in high‐temperature photonic/plasmonic applications.